Reliability and criterion validity of the arrowhead change-of-direction speed test for soccer - Lockie, R. G.; Jalilvand, F. (Facta Universitatis: Series Physical Education and Sport, 2017)
The Arrowhead change-of-direction (COD) speed test was originally designed for soccer, and features three direction changes over a running distance of approximately 37 m. This study aimed to determine the reliability and criterion validity of the Arrowhead test in collegiate soccer players. Twenty Division I female players from the same team completed the Arrowhead test on separate days to assess reliability. Participants also completed tests of linear (30-m sprint; 0-5, 0-10, 0-30 m intervals) and COD (pro-agility and 60-yard shuttle) speed to assess criterion validity. Reliability was determined by intra-class correlation coefficients (ICC) and coefficient of variation (CV). Paired t-tests detected between-session differences in Arrowhead performance. Usefulness was determined by comparing the smallest worthwhile change with a small or moderate effect to the typical error of the Arrowhead test. Correlations were calculated between the Arrowhead test, 30-m sprint intervals, and shuttle tests to assess criterion validity. The ICCs and CVs for both the left- (ICC=0.92; CV=1.01%) and right-turn (ICC=0.93; CV=0.89%) Arrowhead test were acceptable, and the Arrowhead could detect moderate changes in performance. There were no significant between-session differences in Arrowhead times (p=0.87-0.97). Significant relationships were found between the Arrowhead test and the 30-m sprint and 60-yard shuttle (r= 0.55-0.68). Due to relationships with the 30-m sprint and 60-yard shuttle, the Arrowhead test could be utilized to assess a soccer player`s ability to complete longer distance sprints that incorporate direction changes, as opposed to being a test of COD speed.